Peran Manajemen Waktu dan Kedisiplinan Dalam Mempengaruhi Hasil Belajar Optimal - Masayu Endang Apriyanti; Syahid Syahid (Universitas Muhammadiyah Makassar, 2021)
This study aims to analyze the role of time management and discipline on optimal learning outcomes. This research is a survey research with a population of junior high school and senior high school students of the Islamic Education Foundation Nur el Arafah Bekasi. The sample was taken by random sampling technique of 85 people. The instrument used was a questionnaire. Data analysis using multiple regression. From data processing, the results obtained: 1). There is a significant effect of time management and discipline together on optimal learning outcomes as evidenced by the results of the value of Fh = 24.324 and Sig. = 0.000 0.005 2). There is a significant effect of time management on optimal learning outcomes as evidenced by the results of the value of Th = 4.093 and Sig. = 0.000 0.005 3). There is a significant effect of discipline on optimal learning outcomes as evidenced by the results of the value of Th = 3.679 and Sig. = 0.000 0.005. It is better if students are good at using and managing their time very well and effectively because it has a positive impact on optimal learning outcomes and the more productive time they have, the more achievement, the more activities carried out and can be completed on time, so that one day all the ideals are expected or the target set can be achieved optimally. And they should also have strong discipline from an early age so that they are accustomed to doing tasks wholeheartedly, not procrastinating, let alone lazy, because with high discipline all duties and responsibilities can be carried out optimally.